The influence of green attitudes on sustainable consumption in the fashion industry - Hidayat, Taufiq; Sumargo, Albertus Setyo; Zahrudy, Fahrais; Putra, Dimas Bayu Arya (Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of environmental advertising, environmental concern, and the Lifestyle of Health and Sustainability on green attitudes, as well as their effects on sustainable consumption behavior and frugality consumption behavior among Generation Z in Indonesia. This research adopts quantitative research design using cross-sectional survey method. Data were collected from 332 Generation Z respondents in Indonesia through structured questionnaire. The proposed research model was tested using SEM to examine the relationships among the variables. The results indicate that environmental advertising, environmental concern, and the LOHAS lifestyle have a significant positive effect on green attitudes. Furthermore, green attitudes significantly influence both sustainable consumption behavior and frugality consumption behavior among Generation Z consumers. These findings confirm the important role of sustainability-oriented values and lifestyles in shaping responsible consumption behavior. The findings suggest that companies should strengthen environmental advertising strategies that emphasize sustainability values, while governments should enhance environmental education and awareness programs targeting Generation Z. Such efforts can effectively encourage sustainable and frugal consumption practices. This study contributes to the sustainability and consumer behavior literature by integrating environmental advertising, environmental concern, and LOHAS lifestyle in explaining sustainable and frugal consumption behavior on Generation Z consumers